Influence of cooling rate on microstructure development of AlSi9MgMn alloy - Stanić, Davor; Zovko Brodarac, Zdenka (Journal of Mining and Metallurgy, Section B: Metallurgy, 2020)
Aluminum alloys are widely applied in automotive, aircraft, food and building industries. Multicomponent technical AlSi9MgMn alloy is primarily intended for high cooling rate technology. Controlled addition of alloying elements such as iron and manganese as well as magnesium can improve mechanical and technological properties of final casting in dependence from cooling conditions during solidification. High manganese content in AlSi9MgMn alloy together with high cooling rate enables evolution of intermetallic Al15(Mn,Fe)3Si2 phase in globular morphology resulting in enhanced mechanical properties.The aim of this investigation is characterization of AlSi9MgMn alloy microstructure and mechanical properties at lower cooling rates than those for which this alloy was primarily developed. Thermodynamic calculation and thermal analyses revealed solidification sequence in correlation to microstructure investigation as follows: development of primary dendrite network, precipitation of high temperature Al15(Mn,Fe)3Si2 and Al5FeSi phases, main eutectic reaction, precipitation of intermetallic Al8Mg3FeSi6 phase and Mg2Si as a final solidifying phase. Correlation of microstructure features investigation and cooling rate reveals significant Al15(Mn,Fe)3Si2 morphology change from Chinese script morphology at low cooling rate, irregular broken Chinese script morphology at medium one and globular morphology at high cooling rate.
Keywords: AlSi9MgMn alloy, thermal analysis, cooling rate, solidification sequence, microstructure development, mechanical properties